Cost Reduction of Table Fan Design using Design for Manufacture and Assembly (DFMA) - Wee, Soon Chai; Nawawi, Azli (Progress in Engineering Application and Technology, 2021)
Design for Manufacture and Assembly (DFMA) is an integration of Design for Manufacturing (DFM) and Design for Assembly (DFA) Most mechanical engineers or design engineers in engineering studies take DFMA as their guidelines when developing a newly redesigned product. The main objective of this research is to focus on reducing part count and minimizing the cost of the product chosen which is table fan by redesigning and analyzing it using DFMA method. The product would have fewer parts after it has been redesigned, therefore the costs will be minimized and the process of manufacturing and assembly time for the operation will also be affected. The analysis was conducted according to Boothroyd Dewhurst’s method using DFA worksheet. The results revealed that the efficiency design is improved and a greater decrease in the assembly operational time and cost between original and new modified design table fan. The design efficiency of the modified design is 44.2% and the original design is 31.46% which indicates that the greater design efficiency has fewer parts and provides better operational time and cost.